Eating disorder and sports engagement in individuals playing sports - KAYHAN, RECEP FATİH (My University, 2023)
The main purpose of study is to investigate the relationship between the level of sports engagement, eating disorder tendency. A total of 524 individuals, a mean age of 24±8.00 in study. The data of the study were collected using the personal information form, the scale of engagement to sport, the orthorexia-11 scale. In the analysis of the data, the Independet Sample T-Test was used to compare the paired groups to determine the differences between the groups, One-Way Anova was used to compare the groups of three or more. In determining the effect size of the differences, Cohen d values for T-Test and eta2 values for ANOVA were calculated. Pearson Correlation test was used to determine the relationship between eating disorder tendency, sports engagement levels. Participants' sports engagement scores; while it did not differ according to gender (p>0.05), it differed branch, level of sports, diet and year of sports (p<0.05). Orthorexic (eating disorder) tendencies of the participants; while it did not differ gender and level of doing sports (p>0.05), it differed branch, dieting status and year of doing sports (p<0.05). It was determined that the sport, history, diet and training frequency were effective on adherence levels, orthorexic tendency, high level of sport adherence increased orthorexic tendency. Considering that people's physical appearance concerns are high, their desire to have a fit appearance due to environmental effects, this is thought to be effective in increasing the level of engagement to sports, orthorexic tendency

O principal objetivo do estudo é investigar a relação entre o nível de engajamento esportivo e a tendência a transtornos alimentares. Um total de 524 indivíduos, idade média de 24±8,00 em estudo. Os dados do estudo foram coletados usando o formulário de informações pessoais, a escala de engajamento no esporte, a escala de ortorexia-11. Na análise dos dados, o Independet Sample T-Test foi usado para comparar os grupos pareados para determinar as diferenças entre os grupos, One-Way Anova foi usado para comparar os grupos de três ou mais. Na determinação do tamanho do efeito das diferenças, os valores de Cohen d para TTest e os valores eta2 para ANOVA foram calculados. O teste de correlação de Pearson foi usado para determinar a relação entre a tendência ao transtorno alimentar e os níveis de engajamento esportivo. Pontuações de engajamento esportivo dos participantes; enquanto não diferiu quanto ao gênero (p>0,05), diferiu ramo, nível de prática esportiva, dieta e ano de prática esportiva (p<0,05). Tendências ortoréxicas (transtorno alimentar) dos participantes; enquanto não diferiu gênero e nível de prática esportiva (p>0,05), diferiu ramo, regime alimentar e ano de prática esportiva (p<0,05). Foi determinado que o esporte, história, dieta e frequência de treinamento foram eficazes nos níveis de adesão, tendência ortoréxica, alto nível de adesão ao esporte aumentou a tendência ortoréxica. Considerando que as preocupações com a aparência física das pessoas são altas, seu desejo de ter uma aparência em forma devido aos efeitos ambientais, acredita-se que isso seja eficaz para aumentar o nível de envolvimento com esportes, tendência ortoréxica.
Transtorno alimentar e engajamento em esportes em indivíduos que praticam esportes
Keywords: Vício; Nutrição; Exercício; Performance; Imagem Corporal; Transtorno Alimentar; Addiction; Nutrition; Exercise; Body Image; Eating Disorder